Water-Based Metallic Nickel Magnetic Fluids - Viali, Wesley Renato [UNESP]; Assis, Douglas Ricardo de [UNESP]; Couto, Giselle Giovanna do [UNESP]; Melo, Wellington W. M.; Novak, Miguel Alexandre; Jafelicci Junior, Miguel [UNESP] (Amer Scientific Publishers, 2018)
In this work, a metallic nickel water-based magnetic fluid was characterized and its colloidal stability was evaluated over 300 days. Magnetic fluids are colloidal suspensions of a solid phase, usually, nanoparticles dispersed in a liquid, which combines normal liquid behavior and magnetic properties. We report a new route to obtain an aqueous magnetic fluid containing metallic nickel nanoparticles coated with citrate without any further modification of its surface. The citrate-coated Ni nanoparticles were synthesized via a one-pot route by reducing Ni2+ ions with sodium borohydride in presence of citric acid. The Ni nanoparticles were dispersed in O-2-free water to obtain the magnetic fluid. The structural and morphological characterization of the Ni NP were obtained by high-resolution transmission electron microscopy and X-ray diffraction. Magnetic curves were measured using a SQUID-based magnetometer. The colloidal stability of the Ni magnetic fluid was evaluated by dynamic light scattering and zeta potential measurements. The NP had spherical morphology with a diameter of 4.2 +/- 0.7 nm, and the XRD peaks were consistent with a Ni fcc structure. The M-H curve demonstrates superparamagnetic behavior with a magnetization of 6.7 emu/g at 60 KOe and 290 K. The calculated magnetic diameter was 4.18 nm. The hydrodynamic diameter and zeta potential of the MF were measured over 300 days, and no significant changes were observed, which indicates good colloidal stability.
Keywords: Nanofluid; Nickel Nanoparticles; Colloidal Stability